Efficacy analysis of drug-eluting beads transcatheter arterial chemoembolization combining systemic chemotherapy and immune checkpoint inhibitors in unresectable intrahepatic cholangiocarcinoma: a multicenter retrospective cohort study based on propensity score matching - Liu Song; Wang Qingdong; Yin Shunhang; Li Long; Zhao Guangsheng; Yu Guangji; Wang Dong (World Journal of Surgical Oncology)
Abstract Objective To investigate the efficacy and safety of drug-eluting beads transcatheter arterial chemoembolization(DEB-TACE) combined with systemic chemotherapy and immune checkpoint inhibitors in the treatment of unresectable intrahepatic cholangiocarcinoma. Methods This study used retrospective cohort analysis to collect the clinical data of 209 patients with unresectable intrahepatic cholangiocarcinoma treated in Linyi Cancer Hospital, Affiliated Zhongshan Hospital of Dalian University, Affiliated Central Hospital of Dalian University of Technology from January 2020 to January 2024. The patients were divided into observation group and control group based on their treatment plans. The observation group was treated with DEB-TACE combined with systemic chemotherapy and immune checkpoint inhibitor, and the control group was treated with simple systemic chemotherapy and immune checkpoint inhibitor. Based on propensity score matching analysis, the clinical treatment efficacy, survival prognosis, and incidence of adverse reactions of two groups of patients were evaluated. Results 82 patients in the observation group received DEB-TACE combined with systemic chemotherapy and immune checkpoint inhibitors, The control group of 127 patients were treated with systemic chemotherapy and immune checkpoint inhibitors. After a propensity score matching analysis to control for the consistency of patient age, sex, tumor size, tumor number, Child grade, ECOG score, and tumor stage. Propensity score matching analysis created 71 pairs of patients in 2 groups. The objective response rate (ORR, 76.06%) and disease control rate (DCR, 97.18%) in the observed group were significantly higher than that in the control group (52.11%, 85.92%), Progression-free survival (PFS, 10 months) and overall survival (OS, 17 months) were higher than the control group (8 months, 11 months). The Cox proportional hazards model analysis revealed that, Child grade and treatment modality were independent predictors of PFS and OS in patients. The adverse effects during treatment were similar in the two groups, with no statistical difference. Conclusions Compared with systemic therapy alone (systemic chemotherapy + immune checkpoint inhibitor), combined DEB-TACE improves the tumor control rate of patients with unresectable intrahepatic cholangiocarcinoma, extends the survival time and without increasing treatment-related adverse effects, which is a safe and feasible treatment modality.